Microwave-assisted hydrothermal synthesis of Sn3O4 and SnO for electrocatalytic reduction of CO2 to high-added-value compounds - Romeiro, Fernanda da Costa [UNESP]; Martins, Alysson Stefan [UNESP]; Perini, João Angelo Lima [UNESP]; Silva, Beatriz Costa e [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (Springer Nature, 2023)
Sn-based electrocatalysts have recently been applied for CO2 reduction to generate fuels. Here, tin oxide crossed architectures (SnO) and petal-like Sn3O4 semiconductors were synthesized using the microwave-assisted hydrothermal method. The synthesized materials were applied in electrochemical reduction of CO2 and promoted the formation of methanol, ethanol and acetone. The best condition (greatest amount of products) was obtained with − 0.5 V vs Ag/AgCl for both electrocatalysts. For the first time, acetone formation was observed using both SnO and Sn3O4 materials. The SnO electrocatalyst exhibited the best electrochemical activity for CO2 reduction, ascribed to higher charge transfer corroborated by the higher current densities and lower resistance in the Nyquist diagram. Differences in methanol concentration obtained by the samples were ascribed to the different morphology and charge transfer over the films. The results showed that Sn-based electrocatalysts can be applied to generate important products, such as methanol and ethanol, aside from promoting acetone formation. Graphical Abstract: [Figure not available: see fulltext.].